The impact of perceived injury risk and psychosocial factors on walking equity. (March 2023) - Rod, J.E.; King, Mark; Oviedo-Trespalacios, Oscar
Abstract: Walking is the cornerstone of active and sustainable transport. However, traffic safety concerns among pedestrians could reduce walking behaviour. Safety concerns are generally measured through risk perceptions. Unfortunately, a lack of theoretical development of risk perceptions in walking behaviour research has limited our capacity to identify groups of pedestrians who are inequitably affected and address their concerns. To address this gap, the present investigation identified various theory-driven risk dimensions (i.e., mechanism of injury, temporal risk dimensions, and information processing). Logistic and hierarchical linear regression analyses were used to investigate the effect of the risk dimensions on walking behaviour while considering psychosocial factors (e.g., attitudes and social norms). The findings suggest that policymakers and practitioners should consider both objective and perceived pedestrian safety to promote sustainable mobility. Older adults require particular attention as they are inequitably affected by objective and subjective risks.